Mr Robot. Hacking the Apocalypse Mr Robot - John Lynch (Journal for Religion, Film and Media, 2019)
This paper is concerned with the American TV series Mr Robot and its imaginative articulation of key theological and philosophical questions pertaining to authority, reality and belief. As a work of imagination and critique it provides engaging and useful insights into the process of attempting to challenge the technological system that has infiltrated all personal and social relations today, whilst drawing upon a range of key religious ideas and concepts. The article, firstly, locates the series within a frame defined by the concepts of habit and hope as a way of engaging with its form and content. Secondly, it considers the apocalyptic event around which the drama revolves as a system re-set and new beginning that is revealing of a certain kind of truth alongside the subject who speaks to this truth. Thirdly, The central character Eliot's extraordinary ability for computer coding and encryption links to certain ideas about secrets and their role in the notion of authority as that sustained by being in possession of a key that can unlock and, by logical extension also lock, the sanctified data. Lastly, the article addresses perhaps the most powerful aspect of the drama, Eliot's paranoia and psychical fragmentation as he occupies this place on the edge of the system that sees him experience a mental and perceptual breakdown as the cost of his commitment to this act of erasure.